Application of multi-group cfa in analysing moderation effect of socioeconomic attributes on public housing performance - Ishiyaku, B; Kasim, R; Harir, A. I (American Scientific Publishers, 2018)
This study analysed moderation effect of socioeconomic attributes of income and education on public housing performance model using the multi-group confirmatory factor analysis (CFA) method. The objectives of the study was to evaluate the influence of socioeconomic attributes of income and education on public housing performance using occupants’ experience, with a view to proffer recommendations on objective indicator of public housing performance. Literature revealed how little attention is given to effects of socioeconomic attributes on building performance in post occupancy evaluation (POE). This leads to misuse of resources in facilities management. Sample households of 350 were selected in Gombe metropolis, Nigeria, by systematic random sampling to answer questionnaires as the major instrument of data collection. SPSS Version 22 was used for preliminary analyses and AMOS version 21 was used to validate the constructs and develop Structural Equation Model (SEM) of building performance. Results indicated an acceptable SEM model for use in building performance evaluation, with all factor loadings above 0.5 and required fitness indexes achieved. Moderation effect of occupants’ education and income were proved not significant on their experience responses. The finding portrayed occupants’ experience as objective tool for measuring building performance Implication of this finding is in supporting the notion that experience is objective medium of measuring performance than satisfaction. Hence, scholars and professionals in housing should be cautious of the use of these terminologies interchangeably.